Jacinto Iron and steel sheets corporation a production systems study - De la Merced, Karen Grace T. (College of Engineering, 1995)
Jacinto Iron and Steel Sheets Corporation (JISSCOR) is one of the 26 companies of the Jacinto Group of companies. JISSCOR is involved in galvanizing cold-rolled coils to produce iron and steel sheets used for roofing. This production systems study of JISSCOR is composed of seven parts namely: INTRODUCTION, DOCUMENTATION, PROBLEM STATEMENT AND ANALYSIS, SPECIFICATION OF ALTERNATIVES, EVALUATION OF ALTERNATIVES, and RECOMMENDATION AND IMPLEMENTATION. The study also includes areas for further improvement which the company can look into. A brief profile of the company as well as the study?s objectives, scope and limitations are included in the introduction. Documentation of the production process, existing forecasting models used strategies of production planning and organizational chart are specified in the Documentation Section. The study identifies the out-dated machines as the company?s main problem. Analysis of the problem using the stream diagnostic diagram was shown for better understanding. Several alternatives were specified namely: replacement of machine and augmentation of the existing machines. Each alternative is evaluated using different tools such as Cost-Benefit Analysis and Comparison of Costs. The alternative which will provide the company with the largest benefit was recommended. The study also provides a production schedule which the company can use in the implementation of the recommendations. Air wiping operation is introduced in the areas for further improvement section wherein the company can look into the feasibility of using the above-mentioned operation.